State policy on the sedentarization of Tuvans in the Tuvan People's Republic in the 1930s and 1940s - Storozhenko, Alena A.; Nurzat, Arzhaana A. (The New Research of Tuva, 2025)
The article analyzes the initial process of the sedentarization of the Tuvans during the 1930s–1940s in Tuva, which was completed by the late 1950s. A distinctive feature of this process was its relatively late start compared to other nomadic regions. An attempt at a rapid, mass transition of the Tuvans to a sedentary lifestyle and onto “collective rails” at the end of the 1920s was rather quickly abandoned. In 1933, a shift to a new political and economic course began, which encouraged citizens’ private economic initiative. The special status of the Russian population in the Tuvan People's Republic (TPR) as citizens of the USSR also had an influence.The eventual transition of the Tuvans to a sedentary lifestyle was largely the result of the activities of the republican and khoshun settlement committees established in the Tuvan People's Republic in 1940. Based on newly introduced archival documents (from the National Archives of the Republic of Tuva, among others), it has been established that the primary task of the settlement committees in the TPR was to locate sites or land areas suitable for the development of farms, meeting all the necessary living conditions for both people and livestock breeding.The abandonment of the policy of forced and mass sedentarization in the early 1930s, along with the overall delay in the beginning of the process, allowed the Tuvans to gain some time to develop their own adaptive mechanisms.
Keywords: sedentarization; settlement; collectivization; internal migration; nomads; Tuvan People's Republic; arat; Tuvans; kolkhoz; sovkhoz; settlement committee